1999
DOI: 10.1136/jamia.1999.0060122
|View full text |Cite
|
Sign up to set email alerts
|

Driving Toward Guiding Principles: A Goal for Privacy, Confidentiality, and Security of Health Information

Abstract: As health care moves from paper to electronic data collection, providing easier access and dissemination of health information, the development of guiding privacy, confidentiality, and security principles is necessary to help balance the protection of patients' privacy interests against appropriate information access. A comparative review and analysis was done, based on a compilation of privacy, confidentiality, and security principles from many sources. Principles derived from ten identified sources were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 1 publication
0
32
0
Order By: Relevance
“…3 During the training of the team, the need to respect the research subjects' privacy was emphasized, as well as the necessity of confi dentiality of the collected information and of compliance with the norms aiming at data security. 4,17 In the present study, in which subjects and researchers are employed in the same institutions, special care was taken to avoid the direct access of colleagues from the team to private information about the research subjects.…”
Section: Preservation Of Confi Dentiality and Secrecymentioning
confidence: 99%
“…3 During the training of the team, the need to respect the research subjects' privacy was emphasized, as well as the necessity of confi dentiality of the collected information and of compliance with the norms aiming at data security. 4,17 In the present study, in which subjects and researchers are employed in the same institutions, special care was taken to avoid the direct access of colleagues from the team to private information about the research subjects.…”
Section: Preservation Of Confi Dentiality and Secrecymentioning
confidence: 99%
“…At present, research on EMRs focuses on three areas: privacy protection of raw data, access control of EMRs, and privacy-protecting medical information system [3133]. …”
Section: Related Workmentioning
confidence: 99%
“…A recent literature review concluded that despite the need to answer many remaining questions, giving patients direct electronic access to medical records appears to be a positive step. 15 One can envision a time when research networks can be constructed by involving providers and patients with access to selected common data by analysis centers operating under carefully defined rules for data privacy.…”
Section: The Goodmentioning
confidence: 99%